Primitive war [videorecording (DVD)] - Kwanten, Ryan, 1976-; Helfer, Tricia; Wechsler, Nick (Samuel Goldwyn Films, 2025)
Vietnam. 1968. A recon unit known as Vulture Squad is sent to an isolated jungle valley to uncover the fate of a missing Green Beret platoon. They soon discover they are not alone.